Studi In Silico Turunan Imidazopirimidin sebagai Agen Antikanker Payudara terhadap Protein ER-α, ADMET, dan Drug-Likeness - Muhammad Chandra; Fajriah Azra (MASALIQ, 2026)
Breast cancer is one of the leading causes of global mortality, requiring the development of new therapeutic agents that are more effective and selective. This study aims to evaluate the potential of 20 imidazopyrimidine derivative compounds as candidate selective inhibitors of Estrogen Receptor Alpha (ER-α). This study used an in silico approach that included molecular docking using MOE 2019.0102 software with ER-α target protein (PDB ID: 3ERT), followed by drug-likeness screening based on Lipinski’s Rule of Five and prediction of the ADMET pharmacokinetic profile through the SwissADME and pKCSM web servers. The molecular docking results showed that Compound 15 had the strongest binding affinity, with a docking score (S) of -11.94 kcal/mol and a Root Mean Square Deviation (RMSD) value of 0.7 Å, better than the control ligand 4-hydroxytamoxifen (S = -11.1 kcal/mol; RMSD = 1.8 Å). Other potential compounds that showed high affinity were Compound 13 (S = -11.20 kcal/mol) and Compound 1 (S = -10.88 kcal/mol). The ligand-protein complex was stabilized by hydrogen bonds, hydrophobic interactions, and pi-sulfur interactions in the receptor’s active pocket. Physicochemical prediction showed that most compounds met Lipinski’s Rule of Five criteria for oral drug candidates and had good ADMET solubility, permeability, and elimination profiles without indications of hepatotoxicity. The conclusion of this study affirms that imidazopyrimidine derivatives, particularly Compounds 15, 13, and 1, have potential as candidate ER-α-targeted breast anticancer agents. These findings provide an initial contribution to the development of breast anticancer therapy candidates and need to be followed up through experimental in vitro and in vivo studies.